OPTIMALISASI FERMENTASI ETANOL “TERATAI SALJU” DENGAN PALM SUGAR DAN VARIASI SUKROSA - Sarwoko, Jonathan Puji; Sidharta, Boy Rahardjo; Mursyanti, Exsyupransia (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2025)
Abstract "Teratai Salju" is a symbiotic community of bacteria and yeast. One of the fermentation results of "snow lotus" was alcohol that is useful as a solvent such as cosmetics, disinfectants, and fuels. This research aims to determine the genus of microorganisms and the maximum ethanol content produced by "teratai salju" using palm sugar and sucrose variations 15, 45 and 85 grams in 250 ml water with 5 repetitions. Stages of research including growth and maintenance of "snow lotus", observation of colonies morphology, yeast staining, negative staining, Gram staining, dry weight measurement, total acid number, pH measurement, and ethanol content measurement. Data analysis was performed by Analysis of variance (ANOVA) followed by a duncan multiple range test with a 95% confidence level with SPSS 15.0. This research was conducted with a Completely Randomized Design (CRD). The results obtained show that ethanol content of "teratai salju" optimized at the addition of 85 gram sucrose at 0,22-0,86%. Key Words : Ethanol, Fermentation, Sucrose Variation, “Teratai salju”.